Decoding Reed- Muller Codes by Using Hadamard Matrices - Baghdad Science Journal (Baghdad Science Journal, 2009)
This paper discusses the problem of decoding codeword in Reed- Muller Codes. We will use the Hadamard matrices as a method to decode codeword in Reed- Muller codes.In addition Reed- Muller Codes are defined and encoding matrices are discussed. Finally, a method of decoding is explained and an example is given to clarify this method, as well as, this method is compared with the classical method which is called Hamming distance.